Ranma 1/2. Vol. 36 - Takahashi, Rumiko, 1957- (Viz Media, 2006)
After sixteen years, the longest-running manga series in America has finally come to an incredible end! That's right -- this is the conclusion to one of the most outrageous, entertaining and endearing stories the world has ever know. The volume will answer all your questions (no peeking at the end)! Does Ranma break his gender-flipping curse? For that matter, does anybody find a way to reverse the effects of the legendary cursed spring? Does Mousse get Shampoo? Does Kuno finally get his little red-headed pig-tail girl? Does panty-stealing Happosai pilfer enough undergarments to complete his collection? An yes, the ultimate question will be answered: do Ranma and Akane get married?